The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/ene.13887
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of survival and progression in behavioural variant frontotemporal dementia

Abstract: Background and purpose Predicting the course of behavioural variant frontotemporal dementia (bvFTD) remains a major clinical challenge. This study aimed to identify factors that predict survival and clinical progression in bvFTD. Methods Consecutive patients with clinically probable bvFTD were prospectively followed up over an 8‐year period. Baseline neuropsychological variables, presence of a known pathogenic frontotemporal dementia gene mutation and a systematic visual magnetic resonance imaging assessment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
3
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 37 publications
4
23
3
2
Order By: Relevance
“…With disease progression many patients with nfvPPA develop the phenotype of PSP or CBS, which is an adverse prognostic sign [44][45][46][47]. In keeping with these observations, previous survival analyses of frontotemporal dementia (bvFTD and PPA) have shown that reduced letter fluency, motor cortex atrophy and brainstem hypoperfusion were associated with reduced survival [5,48,49]. Our results go beyond these findings, suggesting that development of motor impairments, irrespective of diagnostic group, is an adverse prognostic sign.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…With disease progression many patients with nfvPPA develop the phenotype of PSP or CBS, which is an adverse prognostic sign [44][45][46][47]. In keeping with these observations, previous survival analyses of frontotemporal dementia (bvFTD and PPA) have shown that reduced letter fluency, motor cortex atrophy and brainstem hypoperfusion were associated with reduced survival [5,48,49]. Our results go beyond these findings, suggesting that development of motor impairments, irrespective of diagnostic group, is an adverse prognostic sign.…”
Section: Discussionsupporting
confidence: 89%
“…Prognosis in syndromes associated with frontotemporal lobar degeneration (FTLD) is highly variable and difficult to predict. Disease duration is not fully explained by the diagnostic categorisation to behavioural variant frontotemporal dementia (bvFTD), non-fluent (nfvPPA) or semantic (svPPA) variants of primary progressive aphasia, progressive supranuclear palsy (PSP) or corticobasal syndrome (CBS) [1][2][3][4][5]. Better prognostic models would aid both trial design and clinical management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Второе место после БКЯ в группе деменций с быстрым прогрессированием почти единодушно отводится лобно-височной деменции (ЛВД) и, прежде всего, ее поведенческому варианту [58][59][60][61][62]. Однако исследователи признают, что верификация диагноза ЛВД нередко следует за диагнозом психического заболевания, что искажает представление о скорости прогрессировании болезни [58,63].…”
Section: нозологические различия в скорости прогрессирования деменцииunclassified
“…По мнению авторов, они отражают бóльшую скорость во многом естественного прогрессирования ЛВД в сопоставлении с БА. Дефицит беглости письменной речи и более выраженная атрофия в двигательных отделах коры также рассматриваются в качестве предикторов быстрого прогрессирования ЛВД [62].…”
Section: нозологические различия в скорости прогрессирования деменцииunclassified